A Case of Uterine Prolapse Complicating Pregnancy in Early Second Trimester - Necmiye Döver; Ayla Sargın Oruç; Nuri Danışman; Utku Özcan (Gynecology Obstetrics & Reproductive Medicine, 2011)
Pelvic organ prolapse is a health concern affecting millions of women worlwide. Morover,a woman has an estimated lifetime risk of 11 percent to undergo surgery for prolapse or incontinence.Despite the apparent prevalence of pelvic support problems ,there are few studies of high epidemiologic quality to accurately estimate disease prevalence.But uterine prolapse is a rare condition during pregnancy which can be complicated with severe maternal and neonatal outcomes.We report a case of uterine prolapse and cervical alongation which is first diagnosed at the 17th week of gestation.After the recognation, the patent is administered by both conservative and then non-surgical(pessary) managements. Unique part about our case is early gestastional age at the time of diagnosis and the fact that our patient had only one previous vaginal delivery and no more risk factors for a pelvic organ prolapse with new-onset uterine prolapse in her current(second)pregnancy.In majority of cases pregnancy is superimposed on a preexisting prolapse.Prolapse occurs as a result of relaxation and tearing down of the supportive structures.